The impact of perceived social support and sense of coherence on health-related quality of life in multimorbid primary care patients - Baudendistel, Ines; Miksch, Antje; Götz, Katja; Ose, Dominik; Szecsenyi, Joachim; Freund, Tobias (Chronic illness, 2012)
This study explores the impact of perceived social support and sense of coherence as positive resources for health-related quality of life in multimorbid primary care patients. We analysed cross-sectional survey data on health-related quality of life (EQ-5D), perceived social support (FSozU-K22), sense of coherence (SOC-L9), social demographics and self reported morbidity of 103 multimorbid patients from 10 general practices in Germany. A multiple linear regression model was used to determine the impact of social support and sense of coherence on the health-related quality of life while controlling for age, sex, educational level, marital status and number of chronic conditions. In the final regression model, higher sense of coherence scores were associated with higher health-related quality of life scores (standardized ß 0.34, p < 0.001) whereas a higher number of chronic conditions was associated with lower health-related quality of life scores (standardized ß −0.41, p < 0.001). In the bivariate model, higher perceived social support was associated with higher health-related quality of life scores (standardized ß 0.35, p < 0.001), whereas the model failed to show a significant association after controlling for sense of coherence which is a potential resource for improving health-related quality of life in multimorbid primary care patients. It emerged as a significant element contributing to the prediction of health-related quality of life. This issue may indicate the importance of internal resources for multimorbid patients.